Organization of protection of accounting information in a hybrid war - I. Hrabchuk (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The implementation of economic activity by economic entities occurs in the difficult conditions of conducting hybrid war. It is characterized by the use of specific methods, in particular cyberattacks. Cybersecurity has been proven to be an extension of information security and to cover the protection of an enterprise that uses cyber-media resources and the protection of any other assets that are at risk due to the use of information and computer technology.The article describes the effects of cyber attacks on enterprises that choose stationary and cloud-based software. The inexpediency of using cloud software for large and medium enterprises in a hybrid war is grounded. The tasks at the state level are described, which should be followed to check for malware. A critical analysis of the work of scientists on the evaluation of certain measures for the protection of accounting information is carried out. The measures for minimizing the threats of accounting information at cyber attacks in the part of providing logical (identification of risks, consideration of ensuring information security of the enterprise as part of corporate culture) and physical (data encryption, physical security of technical support) security are substantiated.